Within-subjects verbal lie detection measures: a comparison between total detail and proportion of complications - Vrij, Aldert (Legal and criminological psychology, 2018)
Background. We examined whether the verbal cue, proportion of complications, was a more diagnostic cue to deceit than the amount of information provided (e.g., total number of details). Method. In the experiment, 53 participants were interviewed. Truth tellers (n = 27) discussed a trip they had made during the last twelve months; liars (n = 26) fabricated a story about such a trip. The interview consisted of an initial recall followed by a model statement (a detailed account of an experience unrelated to the topic of investigation) followed by a post-model statement recall. The key dependent variables were the amount of information provided and the proportion of all statements that were complications. Results. The proportion of complications was significantly higher amongst truth tellers than amongst liars, but only in the post-model statement recall. The amount of information provided did not discriminate truth tellers from liars in either the initial or post-model statement recall. Conclusion. The proportion of complications is a more diagnostic cue to deceit than the amount of information provided as it takes the differential verbal strategies of truth tellers and liars into account.